Reduction the electric field effect generated by high voltage on fiber optic cables using metal shielding - Izz K. Abboud; Shahir F. Nawaf; Mohammed H. Dervish (Bulletin of Electrical Engineering and Informatics, 2020)
Because of the fiber optic cables have perfect resistant to weather and environmental effects they can be installed on or with transmission line towers for the power supply control and data communication. To avoid the damages of fiber optic cables, it is used shielded fiber optic cables. Due to the using of this shielding, the electric field that produced from transmission line will be effected .In this paper is studied and compared the influence of metal shielding of fiber-optic cable in the strong electric field which produced by a high voltage transmission line for various types of channel configuration. Based on the results obtained, the metal shielding of fiber optic cables will reduce the electric field strength that lead to good efficiency of communication through the optical cable.